2021
DOI: 10.1016/j.cjco.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome During the COVID-19 Pandemic: State-of-the-Art Review

Abstract: Takotsubo syndrome during the COVID-19 pandemic, state-of -theart review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 83 publications
1
42
0
4
Order By: Relevance
“…2,3,14 It becomes compelling to study and validate these atypical clinical and imaging phenotypes of TTS during the COVID-19 pandemic across data sets from global health resources/registries in order to establish new reference criteria to improve diagnostic specificity and support goal-directed therapy. 2,5 The inpatient mortality of patients with COVID-19 and TTS is much higher than its prepandemic mortality. 10 Although the exact pathologic role of TTS in the adverse outcomes of patients with COVID-19 remains poorly understood, TTS in many patients with COVID-19 infection is likely a unique illness severity marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,14 It becomes compelling to study and validate these atypical clinical and imaging phenotypes of TTS during the COVID-19 pandemic across data sets from global health resources/registries in order to establish new reference criteria to improve diagnostic specificity and support goal-directed therapy. 2,5 The inpatient mortality of patients with COVID-19 and TTS is much higher than its prepandemic mortality. 10 Although the exact pathologic role of TTS in the adverse outcomes of patients with COVID-19 remains poorly understood, TTS in many patients with COVID-19 infection is likely a unique illness severity marker.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Evidence is mounting that increased mortality rates are associated with patients with TTS and COVID-19 infection. 4,5 In the present study, we completed a systematic review of published TTS cases during the COVID-19 pandemic and performed clustering and feature importance analysis on the demographic, clinical, and imaging parameters, aiming to characterize clinical/imaging features and identify mortality correlates.…”
mentioning
confidence: 99%
“…104 Thus, TTS should be considered in the differential diagnosis of COVID-19 patients with cardiovascular complications, although the diagnosis is difficult because cardiac imaging modalities need to be modified to minimize patient contact. 105 Considering the severity of COVID-19, it is better that these patients are diagnosed in the acute phase. Thus, in patients with COVID-19 with cardiovascular complications, TTE evaluation may be useful to guide treatment and determine the need for further invasive workup.…”
Section: Optimizing Care With Other Approachesmentioning
confidence: 99%
“…Precisely, it has been evidenced that the huge emotional stress evocated by the SARS-CoV-2 pandemic can act as a possible TSS trigger. However, it has been reported that TTS may also represent a direct complication of SARS-CoV-2 infection [3,4], and particularly in cancer patients. Cancer patients show different risk factors (i.e., active cancer, surgery, radiotherapy, anticancer drugs), that could determine a coagulation dysfunction, characterized by an increased coagulative activity, and reciprocally by an inhibition of fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the type of cancer and related therapies, such as recent chemotherapy, radiotherapy, surgery, and other concomitant comorbidities (i.e., diabetes, cardiovascular diseases, metabolic syndrome) may increase the rate of vulnerability to the infection and its complications [4]. Furthermore, patients affected by sepsis, neurological disorders (i.e., subarachnoid hemorrhage, seizures, stroke/transient ischemic attack, cerebral tumors, head trauma), and pheochromocytoma, can also develop TTS [3,4]. Drugs, such as dopamine, dobutamine, epinephrine, norepinephrine, and anesthesia drugs, can also represent TTS triggers, evocating a TTS like disorder [5].…”
Section: Introductionmentioning
confidence: 99%